27.5k views
0 votes
-7 (x + 7) = -56

solve for x. i just wanna make sure im right.​

-7 (x + 7) = -56 solve for x. i just wanna make sure im right.​-example-1
User Sevic
by
4.1k points

2 Answers

6 votes

Answer: x = 1

==============================================

There are two ways to solve

First method is dividing both sides by -7, then subtract 7 from both sides like so

-7(x+7) = -56

x+7 = -56/(-7)

x+7 = 8

x = 8-7

x = 1

Or

We could distribute first, add 49 to both sides, then divide both sides by -7

-7(x+7) = -56

-7x-49 = -56

-7x = -56+49

-7x = -7

x = -7/(-7)

x = 1

Either way we get the same result.

--------------------

Checking the answer:

Plug x = 1 into the original equation. Simplify.

-7(x+7) = -56

-7(1+7) = -56

-7(8) = -56

-56 = -56

The answer is confirmed since we got the same number on both sides.

User Obaydur Rahman
by
4.4k points
6 votes

Answer:

x=1

Explanation:

User Jordan Bentley
by
5.4k points